2011
DOI: 10.1080/15438627.2011.608046
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Muscle Actions on the Level of Connective Tissue Damage

Abstract: The aim of this study was to compare the effect of concentric with eccentric muscle actions on the resulting level of damage to connective tissues by urinary concentration of hydroxyproline. Twenty-one male volunteers were divided into control group (CG), experimental concentric group (ECG), and experimental eccentric group (EEG). The measures of hydroxyproline were performed at three times: pretest, fourth week, and posttest. Biceps curl and chest press exercises also were performed with three sets of 10 repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Previous studies have demonstrated that 6-hydroxynicotinate and 2-heptyl-3-hydroxy 4-quinolone are essentially produced from bacterial metabolism2324 and possibly originated from tissue degradation during sample transportation and storage. Hydroxyproline, a major constituent of collagen, is also used as an indicator of tissue damage or degradation25.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that 6-hydroxynicotinate and 2-heptyl-3-hydroxy 4-quinolone are essentially produced from bacterial metabolism2324 and possibly originated from tissue degradation during sample transportation and storage. Hydroxyproline, a major constituent of collagen, is also used as an indicator of tissue damage or degradation25.…”
Section: Resultsmentioning
confidence: 99%
“…The hydroxyproline is formed via post-translational modification of pro-collagen where residues of proline (and lysine) are hydroxylated to form the final collagen product. Hydroxyproline is primarily found in collagen, and the appearance of it in urine can be used as a measure of collagen turnover [45, 46]. It was thus proposed that females from cluster 1 were susceptible to experiencing higher levels of fatigue and pain if they had higher urinary levels of the collagen components hydroxyproline, hydroxylysine and proline.…”
Section: Discussionmentioning
confidence: 99%
“…The formulation of the amino acid supplement was such that it would have provided a direct source of amino acids capable of reducing the requirement for non-myofibrillar catabolism and therefore it had the potential to relieve fatigue. The higher levels of urinary histidine (cluster 1) and glycine (cluster 2) could have contributed to limitations in haemoglobin production and collagen turnover respectively and provision of both histidine and glycine in the supplement may have led to enhancements in the synthesis of these proteins [33, 34, 38, 45] and a reduction in associated symptoms such as fatigue and pain.…”
Section: Discussionmentioning
confidence: 99%
“…4-hydroxyproline is a major component of the protein collagen and declining levels of urinary 4-hydroxyproline are indicative of muscle loss [31]. L-glutamine occupies a major proportion of free intracellular amino acids in the total pool of muscle [32], and degradation level of muscle protein is associated with content of free amino acids like L-glutamine.…”
Section: Metabolic Responses To 520 Days' Isolationmentioning
confidence: 99%